2019
DOI: 10.1063/1.5098335
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry induced group consensus

Abstract: There has been substantial work studying consensus problems for which there is a single common final state, although there are many real-world complex networks for which the complete consensus may be undesirable. More recently, the concept of group consensus whereby subsets of nodes are chosen to reach a common final state distinct from others has been developed, but the methods tend to be independent of the underlying network topology. Here, an alternative type of group consensus is achieved for which nodes t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…As each row of the matrix T is associated to a specific cluster 40 , each one of the blocksB r corresponds to a set of clusters which are identified by the rows of the matrix T. The trivial representation (r = 1) is associated with all the clusters…”
Section: Stability Analysismentioning
confidence: 99%
“…As each row of the matrix T is associated to a specific cluster 40 , each one of the blocksB r corresponds to a set of clusters which are identified by the rows of the matrix T. The trivial representation (r = 1) is associated with all the clusters…”
Section: Stability Analysismentioning
confidence: 99%
“…Previous works on the analysis of multi-consensus have investigated the properties of the network of interaction among agents leading to multi-consensus states [14]- [17]. More in details, the criteria found in [14] are based on the use of Markov chains and nonnegative matrix analysis for fixed and switching topologies, while the existence of multi-consensus is related to the presence of symmetries [15] or of external equitable partitions [16] in the topology. Finally, multi-consensus can be observed also in the presence of delays or differentiation of the dynamics of the units, as shown in [17].…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Symmetries are intimately connected to the spectral peaks of the adjacency and Laplacian matrices [39][40][41], and hence they impact on a wide range of network 'structural measures' [42] and dynamical phenomena. In particular, network symmetries facilitate cluster synchronization [43,44] and can be used to control group consensus [45]. Symmetry in complex networks has received increasing interest recently, in part because it has been shown that many real-world networks have a significant amount of symmetry [46][47][48].…”
Section: Introductionmentioning
confidence: 99%